4-Hydroxyethyl-4-methylmorpholinium chloride - Jun Song (Acta Crystallographica Section E, 2008)
In the title compound, C7H16NO2+·Cl−, the asymmetric unit consists of two cation–anion pairs, in which the ion pairs are interconnected by weak C—H...Cl hydrogen bonds. Each cation forms a network of weak C—H...Cl hydrogen bonds to surrounding chloride ions. The morpholine ring is in a chair conformation. The crystal structure is consolidated by O—H...Cl, C—H...Cl and C—H...O intermolecular hydrogen bonding.